Organización de los cuidados continuos - Gónzalez Barón, Manuel; Valentín, Vicente; Camps, Carlos; Carulla, Juan; Casas, Ana (Psicooncología, 2004)
Continuos care is the integral care to the ill person in his all reality. We have to initiate the integral care to the cancer patient in the diagnostic phase and we have to continuos it along all the evolutive process with a special attention in the final phase, being an essential component in the cancer treatment. The target is to support the best quality of live in the sense of well-being in the physical mental and social status. For that, we need the coordination of the different levels of medical care, to obtain the global target. Continuos care has a lot of scenarios (home, hospital, and hospice) in which the role of different professionals is basic. Symptomatic treatment will be more important along the illness is progressing, but se have to remember that we have to support and treat all the psychological and social needs along all the process.